Metabolic Bone Disease in preterm newborn: an update on nutritional issues - Tagliabue Paolo; Bozzetti Valentina (BMC, 2009)
Abstract Osteopenia, a condition characterised by a reduction in bone mineral content, is a common disease of preterm babies between the tenth and sixteenth week of life. Prematurely born infants are deprived of the intrauterine supply of minerals affecting bone mineralization. The aetiology is multifactorial: inadequate nutrients intake (calcium, phosphorus and vitamin D), a prolonged period of total parenteral nutrition, immobilisation and the intake of some drugs. The diagnosis of metabolic bone disease is done by biochemical analysis: low serum levels of phosphorus and high levels of alkaline phosphatase are suggestive of metabolic bone disease. The disease can remain clinically silent or presents with symptoms and signs of rachitism depending on the severity of bone demineralisation. An early nutritional intervention can reduce both the prevalence and the severity of osteopenia. This article reviews the pathophysiology of foetal and neonatal bone metabolism, focuses on the nutrient requirements of premature babies and on the ways to early detect and treat osteopenia.